A CONCEPTUAL FRAMEWORK IMPLEMENTING AN AS9100 QUALITY MANAGEMENT SYSTEM FOR THE AEROSPACE INDUSTRY - Oschman, Jacobus Johannes (The South African Journal of Industrial Engineering, 2019)
This article proposes, through an extensive review of prominent International Organization for Standardization (ISO) literature, a conceptual framework implementing an AS9100 quality management system (QMS) for the aerospace industry. The conceptual framework developed in this study provides systematic collective knowledge for aerospace industries to understand the most important dimensions, and their mutual relationships, to deliver products and services ensuring customer satisfaction. The article presents a three-phase implementation methodology for achieving sustained success, offering useful practical relevance for any aerospace industry. The approach followed in this study can be used as a foundation for future studies in AS9100 QMS implementation.